Proton-conductive nano zeolite-PVA composite film as a new water-absorbing electrolyte for water electrolysis - M. Nishihara; Y. Terayama; T. Haji; S. M. Lyth; S. Satokawa; H. Matsumoto (eXPRESS Polymer Letters, 2018)
In this study, organic-inorganic composite electrolyte membranes are developed for a novel water-absorbing porous electrolyte water electrolysis cell. As the materials of the composite electrolyte membrane, 80 wt% of a proton-conducting nano zeolite (H-MFI) as an electrolyte and 20 wt% of poly(vinyl alcohol) (PVA) as a cross-linkable matrix are used. The nano zeolite is prepared by a milling process. The nano zeolite-PVA composite membrane precursors are prepared by spraying onto a substrate, followed by cross-linking. The resulting nano zeolite-cross-linked PVA composite films are then evaluated for their properties such as proton conductivity as electrolyte membranes for the water-absorbing porous electrolyte water electrolysis cell. It is confirmed that conventional materials such as zeolites and PVA can be used for the water electrolysis as an electrolyte.